A tale of two epidemics: gay men's mental health and the biomedicalisation of HIV prevention and care in Toronto. Issue 6 (5th March 2019) - Gaspar, Mark; Marshall, Zack; Rodrigues, Ricky; Adam, Barry D.; Brennan, David J.; Hart, Trevor A.; Grace, Daniel
Abstract: There is mounting urgency regarding the mental health of gay, bisexual and other men who have sex with men (GBM). We examined how GBM are understanding the relationship between HIV and their mental health given the increasing biomedicalisation of HIV prevention and care. Our Grounded Theory analysis derived from qualitative interviews with 24 GBM living in Toronto, Canada, including both HIV‐negative and HIV‐positive men. Participants understood biomedical advances, such as undetectable viral load and pre‐exposure prophylaxis (PrEP), as providing some relief from HIV‐related distress. However, they offered ambivalent perspectives on the biomedicalisation of HIV. Some considered non‐HIV‐specific stressors (e.g. unemployment, racial discrimination) more significant than HIV‐related concerns. These men expressed HIV‐related distress as being under control due to biomedical advances or as always negligible when compared to non‐HIV‐specific stressors. Others emphasised the ongoing mental health implications of HIV (e.g. enduring risk and stigma). We describe a tension between optimistic responses to biomedicine's ability to ease the psychosocial burdens associated with HIV and the inability for biomedicine to address the social and economic determinants driving the dual epidemics of HIV and mental distress amongst GBM. We argue for more socio‐material analysis over further sexual behavioural analysis of GBM mental health disparities.